2005
DOI: 10.1590/s1519-566x2005000500011
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de isolados de Metarhizium anisopliae (Metsch.) sorok. contra a cigarrinha da raiz da cana-de-açúcar Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) em laboratório

Abstract: Screening of Metarhizium Anisopliae (Metsch.) Sorok. Strains against the Sugarcane Root Spittlebug Mahanarva Fimbriolata (Stål) (Hemiptera: Cercopidae) in Laboratory ABSTRACT-The accumulated mulch on the soil resultant from the mechanized cutting of sugarcane promotes favorable temperature and moist to Mahanarva fimbriolata (Stål), a pest that causes serious problems due to its widespread occurrence and high populations. Seventy nine isolates of Metarhizium anisopliae (Metsch.) Sorok. from different hosts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 4 publications
0
17
0
11
Order By: Relevance
“…The ability of the fungi to develop the complete cycle is different for each insect, and low percentages of confirmed mortality have frequently been observed, as in studies evaluating the activity of different entomopathogenic fungi against Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) and Collaria scenica (Hemiptera: Miridae) (LOUREIRO et al, 2005;BARBOZA et al, 2011), whereas in a study with Tetraleurodes acaciae (Quaintance) (Insecta, Hemiptera: Aleyrodidae) have found no signs of death caused by fungi in the targeted insects (VILLACARLOS et al, 2003).…”
Section: Pre-selectionmentioning
confidence: 99%
“…The ability of the fungi to develop the complete cycle is different for each insect, and low percentages of confirmed mortality have frequently been observed, as in studies evaluating the activity of different entomopathogenic fungi against Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) and Collaria scenica (Hemiptera: Miridae) (LOUREIRO et al, 2005;BARBOZA et al, 2011), whereas in a study with Tetraleurodes acaciae (Quaintance) (Insecta, Hemiptera: Aleyrodidae) have found no signs of death caused by fungi in the targeted insects (VILLACARLOS et al, 2003).…”
Section: Pre-selectionmentioning
confidence: 99%
“…Coastal sprayers calibrated for a flow rate of 150 L ha −1 (Mendonça, 2005) were used and the insecticide was directed at the stump bases so that 30% of the spray volume reached the stems and 70% reached the sugarcane plant roots (Loureiro et al, 2005). The surfactant Tween ® (0.01% polysorbate 80) was used to treat the fungal suspensions.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that the entomopathogenic fungi and insecticides may have a protracted effect in the field (Dinardo-Miranda et al, 2004a;Loureiro et al, 2005;Tiago et al, 2012). However, although generalizations cannot be made, the cumulative effect is controlled by the weather, the active constituent of the insecticide, the chemical mode of action, and the M. anisopliae isolated to control M. fimbriolata (Dinardo-Miranda et al, 2004a;Loureiro et al, 2005). On other hand, the genetic constitution of the pest population (Quinelato et al, 2012), adaptations and mechanisms of insect resistance (Dubovskiy et al, 2013) may influence the efficiency of the control techniques.…”
Section: Conventional Sampling × New Sampling Method: Between 15 Janumentioning
confidence: 99%
See 1 more Smart Citation
“…Como a maioria das variedades de interesse comercial são suscetíveis às injúrias de ninfas e adultos de M. fimbriolata, pesquisas vêm sendo conduzidas com intuito de avaliar a eficiência de inseticidas e isolados do fungo Metarhizium anisopliae (Metschnikoff, 1879) Sorokin, 1883 (Hypocreales: Clavicipitaceae) para o controle deste inseto (alMeiDa et al, 2003;loureiro et al, 2005;MenDonça, 2005;alMeiDa et al, 2007). Os estudos contribuíram para a implementação de um programa de controle da M. fimbriolata utilizando M. anisopliae e produtos fitossanitários químicos (DinarDo-MiranDa et al, 2004).…”
Section: Palavras-chaveunclassified